THE POST-COMMUNIST ROMANIAN NOVEL – NAVIGATING THE POLITICAL AND SOCIOGRAPHIC DIMENSIONS - VÎRBAN, Iulia-Maria (Studia Universitatis Babeș-Bolyai Philologia, 2025)
The Post-Communist Romanian Novel – Navigating the Political and Sociographic Dimensions. The transition from communism to capitalism in Eastern Europe has been profoundly destabilising, reshaping economic, social, political, and ideological structures. This upheaval not only amplified the uneven development of the Soviet era but also replicated its harshness through neoliberal economic shock therapy, underscoring systemic inequalities between Western centres and Eastern peripheries. Drawing on Wallerstein’s world-systems theory, this relationship symbolises an unequal structural power relationship, with the periphery’s cultural and economic output subjugated to the demands of the centre (WReC, 2015). In literature, these dynamics have triggered a significant genre shift, particularly in the Romanian novel. The memorial and biographical forms increasingly dominate, marking a dissolution of traditional novelistic structures in favour of fragmented, introspective, and hybrid narratives. These forms align with broader trends of precariousness and cultural commodification, mirroring the destabilising effects of transition (Adriana Stan, 2020). Before Romania’s 2007 EU accession, post-communist novels primarily adopted a historiographical approach to document systemic trauma (Vasile Ernu, Lucian Dan Teodorovici, Dan Lungu). Post-accession, these works shifted to a commodified exploration of (post)communist memory, with narratives addressing economic disparities and minority identities (Tatiana Țîbuleac, Liliana Nechita, Adrian Schiop). This shift reflects the master-slave dynamic of centre-periphery relations, where the West’s exoticisation of communist experiences reinforces systemic inequalities. The dissolution of the Romanian novel into memorial and biographical forms symbolises a dual response: a critique of transitional instability and a capitulation to Western frameworks of cultural consumption. REZUMAT. Romanul postcomunist în România – reconfigurări ale politicului și paliere sociografice. Tranziția de la comunism la capitalism în Europa de Est a fost profund destabilizatoare, privitor la impactarea structurilor economice, sociale, politice și ideologice. Această bulversare de tranziție sistemică și-a replicat duritatea prin terapia de șoc neoliberală, subliniind inegalitățile dintre centrele occidentale și periferiile estice. Pornind de la teoria sistemelor-lume a lui Wallerstein, această relație simbolizează un raport de putere structural inegală, arătând cum producția culturală și economică a periferiei e subjugată cerințelor centrului (WReC, 2015). În literatura română, aceste dinamici au declanșat schimbări semnificative, în special în roman. Resuscitarea biografismului și autenticismului domină din ce în ce mai mult, marcând o disoluție a structurilor romanești tradiționale în favoarea narațiunilor fragmentate, introspective și hibride. Aceste forme se aliniază tendințelor mai largi de precaritate și comodificare culturală, reflectând efectele destabilizatoare ale tranziției (Adriana Stan, 2020). Înainte de aderarea României la UE în 2007, romanele douămiiste au adoptat în principal o direcție istoriografică pentru a documenta trauma sistemică (Vasile Ernu, Lucian Dan Teodorovici, Dan Lungu). După aderare, poate fi observată o comodificare a memoriei (post)comuniste, fiind preferate narațiuni care abordează disparitățile economice și identitățile minoritare (Tatiana Țîbuleac, Liliana Nechita, Adrian Schiop). Această schimbare reflectă dinamica stăpân-sclav a relațiilor centru-periferie, în care exotizarea de către Occident a experiențelor comuniste consolidează inegalitățile sistemice. Cuvinte-cheie: memoria (post)comunistă, nostalgia, tranziție, romanul românesc postcomunist, dimensiuni sociografice, teoria sistemelor-lume. Article history: Received 15 June 2025; Revised 11 August 2025; Accepted 30 August 2025; Available online 24 September 2025; Available print 30 September 2025